Quantitative forecasting of problems in industrial water systems - Emerson, A. G. D., 1913- (World Scientific, 2003)
"This textbook is a diagnostic tool. It enables chemical engineers, water technologists and others involved with the design and provision of an industrial water system, while it is still at the design stage, to start with the chemical analysis of a water supply and make a quantitative forecast of the likely problems (scale and corrosion). It is thus possible to make provision for an appropriate water treatment programme from the very outset. The inclusion of a large amount of tabulated data allows results to be read off directly without making complex calculations. This is particularly useful for technologists working on site (for example when "trouble-shooting"). The ability to make quantitative forecasts enables designers to meet accountants on level terms -- by justifying the cost of including a water treatment programme, and by giving a quantitative assessment of the hazards likely to be encountered if the recommended programme is not installed. Methods of water treatment are not discussed in this textbook, since they can change from time to time; the physical chemistry used in quantitative forecasting does not."--Publisher's website.
Supplement, "Alkalinity--pH changes with temperature for waters in industrial systems" at end.
Keywords: Fouling -- Mathematical models.; Corrosion and anti-corrosives -- Mathematical models.; Industrial water supply -- Design and construction -- Mathematical models.; Water -- Analysis -- Tables.; Water chemistry -- Tables.; Water -- Purification -- Tables.; elektronické knihy; electronic books